2016
DOI: 10.1002/cphc.201501206
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Electro‐Optic Kerr Response in a Self‐Stabilized Amorphous Blue Phase with Nanoscale Smectic Clusters

Abstract: We investigated the electro-optic response in the "foggy" amorphous blue phase (BPIII) as well as in the isotropic phase. To the best of our knowledge, such a study has not yet been performed due to the very limited thermal range of BPIII. In this study, we used a single-component chiral bent-core liquid crystal with a self-stabilized BPIII, which is stable over a wide temperature range. The results show that the response time is on the order of hundreds of microseconds in the isotropic phase and increases to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 43 publications
(53 reference statements)
1
2
0
Order By: Relevance
“…For all of the mixtures, the maximum achieved value of K is relatively high, but the highest is produced from the mixture 4 – 2M – NO 2 + 25 wt % S811, with a reported value of 9.2 × 10 –9 m V –2 . This extraordinarily high K value is about 20 times that reported by Le et al in a single-component chiral bent-core material with self-stabilizing BPIII and 10 times what our earlier study found . The maximum magnitude of K in the present BPIII system for all the mixtures, 4 – 2M – NO 2 + 25 wt % S811, 4 – 2M – NO 2 + 35 wt % S811, and 5 – 2M – NO 2 + 35 wt % S811 ( K = 9.2 × 10 –9 m V –2 , K = 1.3 × 10 –9 m V –2 , and K = 1.0 × 10 –9 m V –2 , respectively) outruns the previously reported maximum value by us for a nearly similar system and under the same experimental condition …”
Section: Resultssupporting
confidence: 61%
“…For all of the mixtures, the maximum achieved value of K is relatively high, but the highest is produced from the mixture 4 – 2M – NO 2 + 25 wt % S811, with a reported value of 9.2 × 10 –9 m V –2 . This extraordinarily high K value is about 20 times that reported by Le et al in a single-component chiral bent-core material with self-stabilizing BPIII and 10 times what our earlier study found . The maximum magnitude of K in the present BPIII system for all the mixtures, 4 – 2M – NO 2 + 25 wt % S811, 4 – 2M – NO 2 + 35 wt % S811, and 5 – 2M – NO 2 + 35 wt % S811 ( K = 9.2 × 10 –9 m V –2 , K = 1.3 × 10 –9 m V –2 , and K = 1.0 × 10 –9 m V –2 , respectively) outruns the previously reported maximum value by us for a nearly similar system and under the same experimental condition …”
Section: Resultssupporting
confidence: 61%
“…[22][23][24][25][26][27][28][29][30][31] BCLCs, due to their negative bend-splay elastic constantr atio, if dopedw ith an external chiral agent,c an stabilize the frustrated BPs in the mixture, [32] but single-component BCLCs exhibiting BPs and TGB phases are limited. [33][34][35][36][37][38] Ac ombination of the additional order of bent-corem olecules with molecular chirality provided by the stereocenters present in the chiral moiety can lead to the stabilization of the frustrated phases.…”
Section: Introductionmentioning
confidence: 99%
“…Several strategies are being employed in order to widen the temperature range of BPs and make them viable for device fabrication. , Apart from long-range BPs observed with compounds having dimeric molecular structures, stabilization of BPs has been obtained in composite systems consisting of polymers and LCs , or by incorporation of nanoparticles (NPs). , A hybrid system consisting of a polymer-stabilized BP into which NPs have been doped has been found to further enhance the temperature stability of the BPs . A special feature associated with LCs made of bent-core (BC) molecules is the generation of chirality in spite of the molecules being achiral. , Another approach that has been adopted is to induce BPs by mixing an LC made of achiral BC molecules exhibiting a nematic (N) phase with a N* LC or a nonmesomorphic chiral dopant. BCLCs have been found not only to enhance the temperature range of the BPs but also to contribute to an enhanced Kerr constant. LC dimers formed by linking an achiral BC unit with a chiral rod-like (R) unit via a flexible spacer have been found to possess high molecular chirality, resulting in the formation of a long-range BPIII phase . Stabilization of BPs has been obtained by hydrogen-bonded bent-shaped and T-shaped molecules, featuring a branched terminal group .…”
Section: Introductionmentioning
confidence: 99%